1978
DOI: 10.1161/01.str.9.6.597
|View full text |Cite
|
Sign up to set email alerts
|

Computerized axial tomography in brain death.

Abstract: SUMMARY Two patients with the diagnosis of brain death were evaluated with computerized axial tomography (CAT). After intravenous infusion of 30% Conray there was no visualization of the intracranial vasculature (circle of Willis). The second patient also had an isoelectric EEC A third patient with an intracerebral lesion similar to the other cases but without diagnosis of brain death, showed good visualization of the circle of Willis. Therefore, contrast-enhanced CAT scans can be used as another diagnostic ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Several reasons could explain this result. This method, described for this indication in 1978 [12,13], has benefited from advances in imaging techniques that make it quick and easy to perform. More recent studies showed that a score evaluating the lack of opacification of 7 intracranial vessels allowed confirming cerebral circulatory arrest with high specificity but low sensitivity [6,14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several reasons could explain this result. This method, described for this indication in 1978 [12,13], has benefited from advances in imaging techniques that make it quick and easy to perform. More recent studies showed that a score evaluating the lack of opacification of 7 intracranial vessels allowed confirming cerebral circulatory arrest with high specificity but low sensitivity [6,14].…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-two out of 188 ICUs filled out the questionnaire (a response rate of 44% [10][11][12][13][14][15][16][17][18]. The number of brain dead patients admitted per ICU each year was 11 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings on IVDCT in CCA are in some ways more straightforward and in other ways more complex than past reports would indicate [19][20][21][22]. CT is sufficiently contrast sensitive to detect minor amounts of intracranial intravascular contrast media that would be otherwise missed during conventional angiography.…”
Section: Discussionmentioning
confidence: 71%